The Concept and Practice of Family Life Education - Engler, Ágnes; Kozek K., Lilla; Németh, Dóra (Central European Journal of Educational Research, 2020)
This theorethical article outlines the development of family life education in Hungary. In the early 20th century, as a result of civic initiatives, this specific educational area as an independent professional and scientific field was organized in the United States and Western Europe. In Hungary, however, much like other Central and Eastern European states, institutional education became available much later. A government decree issued in the early seventies draws attention to the fact that "the biological, health, ethical, moral knowledge necessary for harmonious, desirable human relations is not sufficiently widespread among the general public, especially among young people, to create a well-balanced family life and to achieve a broad range of modern family planning. Therefore, measures should be taken to prepare for family life in all forms of public education and in the dissemination of information to the general public” (Mihalec et al 2011, 90) Komlósi points out, however, that despite the first governmental initiative on family life education, for decades there has been no significant change in practice. (Komlósi 1995) ” In Hungarian secondary education, the pedagogical knowledge that can be chosen as subject matter for graduation examinations in pedagogical vocational secondary schools includes a growing proportion of topics related to education for family life.